Coal Depolymerising Activity and Haloperoxidase Activity of Mn Peroxidase from Fomes durissimus MTCC-1173 - Sunil Kumar Singh (Bioinorganic Chemistry and Applications, 2011)
Mn peroxidase has been purified to homogeneity from the culture filtrate of a new fungal strain Fomes durissimus MTCC-1173 using concentration by ultrafiltration and anion exchange chromatography on diethylaminoethyl (DEAE) cellulose. The molecular mass of the purified enzyme has been found to be 42.0 kDa using SDS-PAGE analysis. The values using MnSO4 and H2O2 as the variable substrates in 50 mM lactic acid-sodium lactate buffer pH 4.5 at 30∘C were 59 μM and 32 μM, respectively. The catalytic rate constants using MnSO4 and H2O2 were 22.4 s−1 and 14.0 s−1, respectively, giving the values of cat/ 0.38 μM−1s−1 and 0.44 μM−1s−1, respectively. The pH and temperature optima of the Mn peroxidase were 4 and 26∘C, respectively. The purified MnP depolymerises humic acid in presence of H2O2. The purified Mn peroxidase exhibits haloperoxidase activity at low pH.